Transitional Justice in Times of Conflict: A Case Study of the Barza Inter-Communautaire in the Kivus - Tuenpakdee, Naruemol (Department of Political Studies, 2021)
In the aftermath of the Second Congo War, a range of transitional justice mechanisms was adopted in the ungoverned Kivu provinces in the eastern Democratic Republic of Congo (DRC), characterised by the lack of political settlement, the decline of government control, and the prevalence of different types of violence other than armed fighting. In the wake of this, the Kivus became entangled in a myriad of daunting challenges in their pursuit of justice and sustainable peace, particularly through the formal transitional justice mechanisms introduced by the transitional government. The failure of state-led transitional justice mechanisms led to the implementation of the Barza Inter-Communautaire (Barza) – a local justice mechanism - as a part of a national strategy for reconciliation. In times of ongoing conflict, the Barza was embodied in the constellation of power shaped by local, national and international political dynamics. The Barza-led justice processes during armed conflicts have had both positive and negative impacts on the Kivu provinces. On the one hand, the mechanism - with its restorative potentials - had a pacifying effect on armed conflict since it had the capacity to resolve conflict and de-escalate ethnic violence. On the other hand, the mechanism also had an increasing effect on conflict intensity which would contribute to a greater likelihood of conflict recurrence. This is because the Barza mechanism was capable of being manipulated by warring parties as a part of their political tactics, in conjunction with their military operations. Hence, the manner in which armed conflicts were settled and wrongdoings were addressed through the Barza during the 2003-06 transition had significant implications for conflict dynamics in the Kivu provinces.